Application of Beneish M-Score to Detech Fraudulent Financial Statements in State-Owned Company in Indonesia - Andani, Latifa Putri; Kurniawan, Gatot Iwan (Banking & Management Review, 2024)
Introduction/Main Objectives: This study aims to determine which State-Owned Company are included in the manipulator, non-manipulator, and gray company groups. Background Problems: According to a study conducted in 2016 by the Association of Certified Fraud Examiners, the majority Fraud cases involved 81.2% of government agencies, 8.1% of State-Owned Enterprises, and 2.3% of private companies. The businesses designated by of State-Owned Company caused the most losses to the industrial sector due to fraud at 58.8%. Research Methods: This research uses a quantitative descriptive method. The objects in this study are State-Owned Company companies in Indonesia in 2018-2021. The research sample used a purposive sampling technique. Data analysis was performed using seven types of financial ratios contained in the Beneish M-score method. Finding/Results: The results showed that in 2018 there was 1 company that was included in the manipulator group, 22 companies were included in the non-manipulator group, and no company was included in the gray company group in 2018. Then in 2019 there were 3 companies that were included in the manipulator group, 17 companies are included in the non-manipulator group, and 3 companies are included in the gray company group. In 2020 there were 5 companies included in the manipulator, 16 non-manipulator companies, 2 companies included in the gray company group. And in the last year, namely 2021, there will be 1 company that is included in the manipulator group, 22 non-manipulator companies, and no company that is included in the gray company group in 2021.